Amphetamine users and crime in Western Australia, 1999–2009 - Jennifer Fleming
This current study aims to examine the relationship between amphetamine use and crime among police detainees in Western Australia. Further, the study provides a brief profile of detainee amphetamine users and compares this with the profile of a non-user. Amphetamines have been increasingly available on Australian drug markets since the early 1990s (National Drug Research Institute 2007). Clandestine laboratory detections increased from 50 in 1996 to 250 in 2002 (Ministerial Council on Drugs Strategy 2004), although use decreased slightly in the general population between 2004 (3.2%) and 2007 (2.3%) (Australian Institute of Health and Welfare 2008). There has also been an increase in the amount of high-grade amphetamine detected by Customs and the Australian Federal Police (AFP). Amphetamine use has been associated with psychological, physical and social harm, criminal behaviour and violence (Dyer & Cruickshank 2005; Lynch, Kemp, Krenske, Conroy & Webster 2003; Wickes 1993). The Drug Use Monitoring in Australia (DUMA) project has collected data since 1999. This current study aims to examine the relationship between amphetamine use and crime among police detainees in Western Australia. Further, the study provides a brief profile of detainee amphetamine users and compares this with the profile of a non-user